CHILD MARRIAGE AMONG THE TRIBAL COMMUNITIES OF WAYANAD:THE ROLE OF LOCAL SELF GOVERNMENTS TO COMBAT THE SITUATION - E.G.JOSEPH (AKG CENTER FOR RESEARCH AND STUDIES, 2015)
Among the child marriages that have taken place in the world,40% are reported from India.In India about six crore women are getting married in an year.Out of which 2.4 crore brides are girls.The reasons for child marriage are poverty,educational backwardness,rituals,traditions etc.Child marriage is a social evil.It cannot be eliminated with a law or punishment.The Prevention of Child Marriage Act 2006 is in force in our country.People are ignoring this Act and encouraging child marriage under the pretext of religious beliefs,customs and traditions.The National policy of population announced in 2000 by the Govt.of India said that late marriage of women should be encouraged.The National policy for the empowerment of women 2001 exhorted that by the end of 2010 child marriage system in our country should be tackled fully.The National policy on youth announced that nationwide conscientisation work should be undertaken regarding the marriageable age of boys and girls.But the situation has not been changed.Among the 20 countries in the world where the number of child marriage is high,India occupies 11th place .Out of the two marriages held in India one is a child marriage.